(untitled) (Annals of Medical Research, 2024)
Aim: This study aimed to determine the association connection vitamin D level and demographics, duration of pain, pain intensities, neuropathic pain intensities, functional abilities, and quality of life in patients with chronic mechanical low back pain. Materials and Methods: After blood samples were taken to analyze serum 25 hydroxyvitamin-D, the participants were organized into two groups: those with vitamin D level >20 ng/mL, which was considered sufficient or insufficient, and those with level ≤20 ng/mL, which was considered deficient. The participants’ resting, activity, and night pain levels were recorded with the visual analog scale (VAS), neuropathic pain using Douleur Neuropathic 4 (DN4), functional abilities using the Oswestry Disability Index, and quality of life using the 36-item Short-Form Health Survey. Results: This study included 157 participants. The patients in the vitamin D level >20 ng/mL group were considerably older than those in the vitamin D level ≤20 ng/mL group. Furthermore, the vitamin D level >20 ng/mL group had higher educational level than the other group. While the vitamin D level >20 ng/mL group had lower VAS-resting and VAS-activity scores than the vitamin D level ≤20 ng/mL group, no meaningful disparity was detected between them in terms of night pain VAS score, DN4, pain duration, disability, and quality of life. Conclusion: The results indicated that differences exist between vitamin D deficiency and chronic low back pain in terms of age, educational level, smoking, and pain level. According to the results, vitamin D level in patients with chronic low back pain was correlated with young age, smoking habit, low educational level, and high pain level.